The Lonchaeidae of Fiji (Diptera: Schizophora) - Macgowan, Iain (Zootaxa, 2014)
The status of the family Lonchaeidae on the islands of the Fiji group is reviewed. Data are provided from trapping undertaken as part of the NSF-Fiji Terrestrial Arthropod Survey and from Fijian Lonchaeidae in the collections of the Bishop Museum, Hawaii and the Natural History Museum, London. Five new species, Lonchaea fiji sp. nov., Lonchaea melanesia sp. nov., Lonchaea vanua sp. nov., Silba kadavu sp. nov. and Silba setiphallus sp. nov. are described. Two species new to Fiji, Dasiops ruidifrons McAlpine, 1964 amd Lamprolonchaea lustrata McAlpine, 1964, are recorded. Five species previously recorded, Lamprolonchaea brouniana (Bezzi, 1919), Lamprolonchaea smaragdi (Walker, 1849), Lonchaea cyaneoneitens Kertész, 1901, Silba calva (Bezzi, 1913) and Silba setifera (de Meijere, 1910) are re-evaluated and are removed from the checklist. The fauna is now considered to comprise of 11 species in 4 genera. A key is provided to the Lonchaeidae present on the islands.